Pola Asuh Otoriter, Intensitas Menonton Tayangan Kekerasan dan Kecenderungan Agresif Anak Sekolah Dasar - Lilia, Lilia; Djalali, M. As'ad (Persona:Jurnal Psikologi Indonesia, 2014)
Abstract. There are a lot of films are screened andvarious games which one liked by children nowadays. Those movies and games which are usually contain a lot of challenges , however  not all of them positive influence. The films and games which contain negative influence can stimulate the child agrgressively, especially the ones which contain violence. Authoritarian parenting is also a factor that affects the aggressiveness of the child. Parental upbringing violent without any compromise can lead to rebellion and an aggressive stance on the aggressive behavior of a child, then the child will be more visible on the child's social relationships . The purpose of this study is to determine the relationship between authoritarian parenting and watching intensity level of aggressiveness of violence against children . The theory used is the social learning theory (social learning theory ) . The approach is using  quantitative research methods . The population was grade 5 of elementary school students . The results showed that there is no  absence relationship between authoritarian parenting and watching intensity level of aggressiveness towards children .  Keywords : authoritarian parenting, watching intensity of violence; child's level of aggressiveness